Inaugural Section Special Issue Key Topics and Future Perspectives in Natural Hazards Research - Tapete, Deodato (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book collects selected high-quality papers published in 2018-2020 to inaugurate the "Natural Hazards" Section of the Geosciences journal. The topics encompass: trends in publications at international level in the field of natural hazards research; the role of Big Data in natural disaster management; assessment of seismic risk through the understanding and quantification of its different components; climatic/hydro-meteorological hazards; and finally, the scientific analysis and disaster forensics of recent natural hazard events. The target audience includes not only specialists, but also graduate students who wish to approach the challenging, but also fascinating